THE EFFECT OF EDUCATIONAL BACKGROUND AND WORK EXPERIENCE ON THE WORK ETHIC OF EMPLOYEES - Arwen Pawennei; Abdul Nasir Rachman (Journal of Entrepreneur, Business and Management, 2023)
The aim of this research is to analyze the influence of educational background and work experience on the work ethic of PT employees. Sulawesi Mandiri Pratama both partially and simultaneously. This research is causal associative research using quantitative research. Based on the results of the research and discussion, the following conclusions can be drawn are there is a positive and significant influence between educational background variables on employee work ethic at PT. Sulawesi Mandiri Pratama; There is a positive and significant influence between the work experience variable on the work ethic of employees at PT. Sulawesi Mandiri Pratama; There is a positive and significant influence between educational background and work experience simultaneously on the work ethic of employees at PT. Sulawesi Mandiri Pratama. Keywords: work experience, educational background, employees